Trapdoor Fracture in a Child Following a Domestic Accident: Case Report - Azenha, Marcelo Rodrigues; Kato, Rogerio Bentes; Cunha Junior, Célio Armando Couto da; Rodrigues, Jorge Alex Pereira; Taveira, Antonio Pablo Siqueira; Oliveira, Elker Silva de (Brazilian Journal of Case Reports, 2024)
The trapdoor fracture is a subtype of orbital fracture and is considered a rare condition that occurs primarily in children and adolescents. The treatment consists of surgery to access and remove the trapped tissue in the floor of the orbit that prevents the movement of the eyes on the affected side. The aim of this article is to present a case of a trapdoor fracture in a 4-year-old child who suffered a domestic accident and underwent surgery under general anesthesia to release the muscles trapped in the orbital floor. The postoperative outcome was considered excellent, with complete recovery of visual and aesthetic functions, without the need for reconstruction of the fractured region with any type of fixation material.